Gender Equality in Women's Representation as Election Supervisors on the Island of Kalimantan: A Civic Education Perspective - Ricky Santoso Muharam; Danang Prasetyo; Sudaryatie Sudaryatie; Vina Dini Pravita; Natalia Heni Primawati (Universitas Negeri Semarang, 2026)
This study aims to analyze the representation of women as members of Bawaslu throughout Kalimantan using Dahlerup's critical mass theory and Anne Phillips' perspective of political representation. The method used is a mixed-methods approach, namely, quantitative statistical analysis of the proportion of female members in each district/city, as well as a qualitative study of structural and cultural factors that affect women's participation. The results of the study show that the majority of regions in Kalimantan have not reached the critical mass threshold of 30% female representation, and six regions have nonfemales members at all. The main obstacles found include a recruitment process that is gender-neutral but not responsive to women's needs, a lack of institutional support, and the dominance of patriarchal norms. Analysis with Phillips' theory confirms that the numerical presence of women does not guarantee substantive advocacy of gender issues without the support of an inclusive political environment. The scientific contributions of this study include: (1) the latest and comprehensive mapping of the level of women's representation as election supervisors in Kalimantan; (2) the integration of critical mass theory and representational politics to analyze the relationship between numerical presence and substantive advocacy; (3) an adaptive civic education intervention model to improve women's political literacy and self-confidence; and (4) data-driven affirmative policy recommendations to strengthen democratic integrity and political inclusivity in Indonesia. This study recommends strengthening gender quota enforcement, reforming recruitment mechanisms, expanding women’s civic education, and implementing data-driven monitoring to promote meaningful women’s representation in election oversight in Kalimantan.